Gender differences in first-year College students’ academic expectations - Diniz, António M. (2019)
Based on a multidimensional definition of academic expectations (AEs), we examine students’ AE component scores across countries and genders. Two samples (343 Portuguese and 358 Spanish students) completed the Academic Perceptions Questionnaire (APQ) six months after enrolling in their universities. Factorial invariance was ensured across countries and genders, allowing us to study AEs using the APQ for both genders and in both countries. No significant differences in factor means were found between countries, indicating that AEs are not an obstacle to student mobility. Gender differences were found in some AE factor means, Training for employment, Personal and social development, Student mobility, Political engagement and citizenship, and Social pressure, with males exhibiting higher scores. Because these differences are not supported by most literature in this domain, further studies are needed to clarify the causes of women’s lower expectations and, therefore, risk of adaptation difficulties.